Kemampuan Guru Mengembangkan Instrumen Tes Hasil Belajar, dan Karakteristik Soal yang Dihasilkan - Bambang Budi Wiyono dkk Bambang Budi Wiyono dkk (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This study aimed to investigate the construction process of achievement test used at UM’s Laboratory junior high school and to find out the validity, reliability, discriminating power, and difficulty index of the tests. The achievement test analyzed were those used in these subject: Bahasa Indonesia, English, Science, Mathematics, Social Science, and civics. The results show that construction process was good, except for item analysis. Additionally, most tests had good validity and reliability, but some tests had low discriminating power.